Break and Fix It (Brick It) Training: Improving Problem Solving Skills in Student Organizations - Pralayar Fanny Fadesti; Dian Dwi Nur Rahmah; Edoardo Tondang; Dwi Rizkie Maulidah Pratiwi; Putri Sadewi Meiindry; Maya Aprilia Christy; Nailah Alda Salsabila; Ikbar Raya Nugroho; Djian Adeilia Alfaeni; Dyahsari Mutmainnah (Plakat : Jurnal Pelayanan Kepada Masyarakat, 2025)
Student organizations require effective problem-solving skills to navigate challenges and achieve their goals. This community service activity was conducted in response to identified issues within the Himpunan Mahasiswa Program Studi Komunikasi dan Penyiaran Islam (HMPS KPI) at UIN Sultan Aji Muhammad Idris Samarinda, including unclear task divisions and misaligned work programs. Adopting an experiential learning approach, 16 members attended the training, which centered on using a fishbone analysis diagram to deconstruct organizational problems. The program's effectiveness was assessed using two levels of the Kirkpatrick evaluation model. Level 1 (reaction) was measured via a satisfaction questionnaire, and Level 2 (cognitive) was measured using a pre-test and post-test design analyzed with a paired sample t-test. The results indicated a highly positive reaction from participants, with 100% rating the training material and benefits as excellent. The cognitive evaluation showed an 8% increase in participants' understanding, with the mean score improving from 58.25 (pre-test) to 66.25 (post-test). Although this increase was not statistically significant (p > 0.05), qualitative feedback confirmed that the training positively impacted the organization by fostering increased participation and enhancing members’ problem-solving abilities. The training successfully provided practical skills, leading to improved organizational dynamics and performance.